Identification of Specifications and Catches of Garok Clamps at Bondet Coastal Fishery Port (PPP), Cirebon Regency - Evi Susilawati (Barakuda'45, 2022)
Class Pelecypoda or Bivalves include clams, oysters, mussels and the like. Basically Pelecypoda has a unidirectional shell and a mantle in the form of two bilaterally symmetrical auricles or lobes. Clams do not have a radula like gastropods and do not have a distinct head or tentacles. Blood clam (Anadara granosa) is a type of clam that belongs to the Pelecypoda class. This research aims to identify tool specifications, catch yields, selectivity and productivity of scallop fishing gear operated in the waters of Cirebon Regency, West Java. The research was carried out in April-June 2022 in Gunungjati District. Measurement of fishing gear was carried out along the fishing village of Bondet Coastal Fishery Port (PPP) Cirebon Regency. The method used is a case study method with quantitative descriptive analysis to determine the specifications of the tools and catches taken by interviewing fishermen. The research results show that clam shells are included in the dredge gear category. The components consist of a body mouth, garok, frames, nets, and ropes of various sizes. The constituent materials used are iron and stainless steel, weighing up to 50 kg. The main catch of garok clams in Cirebon Regency consists of blood clams (Anadara granosa.) and by-catch in the form of several demersal fish, comprising 7 species. This tool is classified as non-selective because of its construction which has a net with a small mesh size (2-5 inches), so that this tool catches many species with different sizes of bycatch of 74.76%. The productivity of garok sea cucumbers is carried out using the swept area method, with an average catchment area of 0.0242 km2 and a catch rate of 15.058 kg/hour.